Hysteresis in stabilization of methane diffusion flames with plasmas. (1st September 2016) - Tang, Jingfeng; Wei, Liqiu; Song, Jian; Yu, Daren
Highlights: The liftoff and reattachment velocities are strongly affected by plasmas. The hysteresis regime is reduced and eventually disappeared with the addition of plasmas. A topological approach is used to predict the change of flame structures in hysteresis region. Abstract: The stabilization characteristics of liftoff and reattachment in methane diffusion flames have been investigated experimentally with addition of plasmas. The flame liftoff and reattachment velocities have been measured by varying the applied voltages on plasmas. The results show that the liftoff and reattachment velocities are strongly affected by the plasmas. The difference between these two velocities as well as the flame hysteresis region is reduced and eventually disappeared with the addition of plasmas. A topological approach is put forward to explore the mathematic laws of hysteresis phenomena, and the existent hysteresis and catastrophe laws of flame structure transition are interpreted under the typical operation routes. It is concluded that a change of flame stabilization will occur when the fuel velocity or the applied voltage passes through stabilization boundaries in a special direction.